The Auditory System of the Dipteran Parasitoid Emblemasoma auditrix (Sarcophagidae) - Tron, Nanina; Stölting, Heiko; Kampschulte, Marian; Martels, Gunhild; Stumpner, Andreas; Lakes-Harlan, Reinhard; Justus Liebig University Giessen (My University, 2016)
Several taxa of insects evolved a tympanate ear at different body positions, whereby the ear is composed of common parts: a scolopidial sense organ, a tracheal air space, and a tympanal membrane. Here, we analyzed the anatomy and physiology of the ear at the ventral prothorax of the sarcophagid fly, Emblemasoma auditrix (Soper). We used micro-computed tomography to analyze the ear and its tracheal air space in relation to the body morphology. Both tympana are separated by a small cuticular bridge, face in the same frontal direction, and are backed by a single tracheal enlargement. This enlargement is connected to the anterior spiracles at the dorsofrontal thorax and is continuous with the tracheal network in the thorax and in the abdomen. Analyses of responses of auditory afferents and interneurons show that the ear is broadly tuned, with a sensitivity peak at 5?kHz. Single-cell recordings of auditory interneurons indicate a frequency- and intensity-dependent tuning, whereby some neurons react best to 9?kHz, the peak frequency of the host s calling song. The results are compared to the convergently evolved ear in Tachinidae (Diptera).
Keywords: parasitoid fly; morphology; tympanate ear; single-cell physiology; micro-computed tomography; ddc:570